Understanding language contact: A comprehensive methodological approach to studying the Volga Germans in Argentina - Ladilova, Anna (Bergen Language and Linguistics Studies, 2025)
The current article provides an overview of the mixed-methods design, including online research, qualitative interviews, quantitative questionnaires, visual documentation and participant observation in three Argentine provinces, applied in the context of the research project “Collective Identity Construction in Migration: A Case Study of the Language Contact Situation of Volga Germans in Argentina” (Ladilova 2013). The aim of this study was to conduct a formal analysis of language contact phenomena, with a special focus on transference and code-switching, as well as an in-depth exploration of the construction of collective identity. From the extensive dataset of 96 narrative interviews and almost 450 questionnaires, the final analysis focuses on 12 narrative interviews and 381 questionnaires, offering a nuanced understanding of the dynamics of language contact and cultural preservation among Volga Germans in Argentina. I will discuss the processes of (a) developing the methodology during the study, (b) selecting the data that I finally decided to include in the analysis, and (c) bringing together the different types of data in the article.